Prophage landscapes in clinical MRSA: safety profiling and discovery of Lys81, a broad-spectrum bacteriolytic enzyme - Fangfei Ran; Minglei Yang; Xiuxiu Zeng; Hui Su; Jiayi Dong; Guosheng Gao; Airong Hu; Yaoren Hu; Yuechao Sun (Frontiers in Microbiology, 2026)
Introduction Methicillin-resistant Staphylococcus aureus (MRSA) poses a significant threat to global healthcare, requiring novel therapeutic strategies. Prophages, latent phage genomes integrated into bacterial chromosomes, are important resources for antimicrobial development due to their genomic stability and genetic engineering potential. Methods In this study, we performed genomewide sequencing on 329 MRSA isolates to predict prophage sequences, followed by analyses of these prophages—including examinations of virulence genes, antibiotic resistance genes, homologous proteins of pathogenic MRSA phages, and functional predictions of these homologous proteins—to evaluate their safety and value as genetic engineering scaffolds and to screen for novel broadspectrum bacteriolytic enzymes. Results Our data indicate that 85.7% (282/329) of strains carried complete prophage sequences; 64 strains lacked virulence factors or genes, meeting the core criteria for safe vectors. Resistance screening found only 6 prophages carried msrA , confirming the biosafety of the remaining strains. A significant correlation existed between prophage virulence gene capacity and genomic structure (R 2 = 0.99986684, p = 3.64e-69). High-virulence clusters (>10 factors) showed high structural similarity; 10 characteristic sequences linked to S. aureus phages and their prevalence patterns were identified via conserved motif analysis. Collinearity analysis with reference to virulent MRSA phages and 3D structural predictions of orthologous proteins identified two lysozymes and a host-recognition device. Notably, Lys81, an N-acetylmuramoyl-L-alanine amidase ortholog, was prioritized and characterized as a broad-spectrum lytic enzyme. Our data show Lys81 has key properties: (1) Broad-spectrum antibacterial activity, lysing 52.3% (23/44) of clinical S. aureus strains and cross-acting against Gram-positive bacteria such as Pseudomonas aeruginosa and Listeria ; (2) Excellent environmental adaptability, maintaining activity at pH 5.0 and 0°C, with 25 mM Na + and Ca 2 + enhancing function; (3) Potent biofilm clearance, achieving 83% MRSA biofilm reduction at 50 μg/mL; and (4) Favorable in vivo safety/efficacy, eradicating MRSA infections in lung organoid models with minimal cytotoxicity. Discussion This study establishes a theoretical foundation for the clinical translation of MRSA prophages, positioning Lys81 as a novel candidate for treating drug-resistant bacterial infections.